2019
DOI: 10.1111/jocn.14823
|View full text |Cite
|
Sign up to set email alerts
|

Flawed self‐assessment in hand hygiene: A major contributor to infections in clinical practice?

Abstract: AimTo assess the quality of self‐assessment and the attitude of healthcare workers (HCWs) to hand hygiene (HH) as possible factors of unsatisfactory HH compliance in clinical practice.BackgroundNoncompliance of HH causes healthcare‐acquired infections (HAI) in patients. It is assumed that HH‐related infections make up approximately 80% of all infections in clinical practice. Our observations suggest that self‐assessment and attitude might be surprisingly important factors.Design and methodThe cross‐sectional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 48 publications
3
19
0
Order By: Relevance
“…However, this latter association may have been artificially increased by social desirability bias and thus does not represent true clinical adherence, as has been previously reported for other IPC measures such as hand hygiene. 24 Finally, the reported use of respirators (FFP2/N95 masks) showed a protective effect with lower seropositivity. This observation might reflect either true protection or residual confounding (eg, higher general adherence to IPC recommendations), which needs to be elucidated in welldesigned clinical trials.…”
Section: Discussionmentioning
confidence: 94%
“…However, this latter association may have been artificially increased by social desirability bias and thus does not represent true clinical adherence, as has been previously reported for other IPC measures such as hand hygiene. 24 Finally, the reported use of respirators (FFP2/N95 masks) showed a protective effect with lower seropositivity. This observation might reflect either true protection or residual confounding (eg, higher general adherence to IPC recommendations), which needs to be elucidated in welldesigned clinical trials.…”
Section: Discussionmentioning
confidence: 94%
“…Self-reported hand hygiene behaviour was higher than observed data in most studies (n=11). The greatest differences were 31% self-reported versus 6% observed hand hygiene in the general public in Peru 80 , and 67% self-reported versus 15% observed hand hygiene in healthcare workers in a large hospital in Vietnam 72 . In the only study that examined it, face covering wearing was self-reported at 25% but observed at 1% in emergency department personnel at a Minnesota public teaching hospital 67 .…”
Section: Resultsmentioning
confidence: 92%
“…Of 18 studies investigating other infectious diseases, most studies (n=15) looked at hand hygiene in a healthcare worker population 63, 64, 66, 6877, 79, 80 , while two studied it in the general public 65, 78 . One studied face covering use in healthcare workers 67 .…”
Section: Resultsmentioning
confidence: 99%
“…WHO and HIPAC guidelines reported very low HH compliance among HCWs (7). In 2010, Erasmus et al reported average compliance values of around 40% (19) which started to improve after WHO's "Clean care is safer care" initiative, but the rate of HH adherence and knowledge varies significantly between countries with some specifics for Eastern Europe (13,20,21), often accompanied by flawed self-confidence of HCWs (22). Thus, we cannot rule out the importance of inappropriate examples of HH compliance provided by hospital stuff during the educational process.…”
Section: Discussionmentioning
confidence: 99%